Bifurcación alta de la arteria braquial - Rojas Vega, Tomás (2014)
Normal anatomy describes the way in which the body of most living beings is arranged; however, there is up to 40% of individuals in which variations of these patterns can be found without this meaning association with a pathological event. According to the findings of the present corpse’ study, done on corpses of the University of Costa Rica’s Anatomy Department during the months from June to December of 2013, high bifurcation of the braquial artery (above the antecubital fossa) can be found as an anatomical variation in up to 18, 8% of individuals and can be bilateral in near 50% of them.